Exploring Factors that Correlate to Student Pre-Service Teacher Retention in RQA Learning Models - Wulandari Saputri; Panggih Priyambodo; Setia Budi; Fahmy Armanda (AL-ISHLAH: Jurnal Pendidikan, 2022)
Retention is the key to the success of a learning program. Several studies have shown that retention can be influenced by metacognitive skills, critical thinking, cognitive learning outcomes, and applied learning models. Meanwhile, testing the relationship between the three factors mentioned above and retention is only done using simple and multiple regression with two factors. This correlational study was conducted to determine the relationship between three factors, namely metacognitive skills, critical thinking, and cognitive learning outcomes on retention in students taught by RQA and QASEE learning models, as well as conventional learning. A total of 107 pre-service teachers of Biology Education students in South Sumatra, Indonesia, were involved in this study. The results showed a relationship between metacognitive skills, critical thinking, and cognitive learning outcomes with retention in students who were taught the RQA learning model. However, in the QASEE learning model and conventional learning, this relationship was not found. Thus, it can be concluded that more than two factors affect retention. Then, applying the appropriate learning model also influences the success of a learning program. Finally, conventional learning that only emphasizes efforts to get students to pass the exam must be abandoned immediately.